How to recognize potential school leaders among primary school teachers : framework based on financial literacy level and type of motivation - Filipović, Jelena, ekonomistica (Array, 2019)
The aim of this paper is to discuss the potential of primary school teachers for governing roles in schools. The level of teacher’s financial literacy is used as a proxy for their managerial potential – managerial competences. Using the Competence Motivation Theory as framework, the authors postulate that teachers with the higher perceived competence in financial literacy are at the same time intrinsically motivated to achieve mastery in this field. Therefore, the teacher’s perceived competence and type of motivation are combined with a set of individual and contextual determinants, highlighted in the previous research, and the framework for assessing teacher’s potential or aptness for the governing position in the school is proposed. The design of this framework is based on data collected via survey which included 954 primary school teachers from Serbia, and analysed by linear and multinomial regression and cluster analysis. The results demonstrate that teachers can be categorized into four different groups, with variable degree of their potential for the governing roles. Clusters vary according to teachers’ gender, subject they teach, location of the school, level of education and whether they are driven by extrinsicor intrinsic motivators.